2018
DOI: 10.1159/000493551
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial Comparing Proactive, High-Dose versus Reactive, Low-Dose Intravenous Iron Supplementation in Hemodialysis (PIVOTAL): Study Design and Baseline Data

Abstract: Background: Intravenous (IV) iron supplementation is a standard maintenance treatment for hemodialysis (HD) patients, but the optimum dosing regimen is unknown. Methods: PIVOTAL (Proactive IV irOn Therapy in hemodiALysis patients) is a multicenter, open-label, blinded endpoint, randomized controlled (PROBE) trial. Incident HD adults with a serum ferritin < 400 µg/L and transferrin saturation (TSAT) levels < 30% receiving erythropoiesis-stimulating agents (ESA) were eligible. Enrolled patients were randomized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 43 publications
2
31
1
1
Order By: Relevance
“…Moreover, hardly any information from prospective trials is available regarding optimal therapeutic targets (e.g., hemoglobin or ferritin levels), which, however, may be different according to the underlying disease. One pioneering study (PIVOTAL for Proactive IV Iron Therapy in Hemodialysis Patients) addressed some of these end-points (risk of death, major adverse cardiovascular events, and infection) in patients undergoing hemodialysis and has just been published [149,150]. A high-dose regimen of i.v.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Moreover, hardly any information from prospective trials is available regarding optimal therapeutic targets (e.g., hemoglobin or ferritin levels), which, however, may be different according to the underlying disease. One pioneering study (PIVOTAL for Proactive IV Iron Therapy in Hemodialysis Patients) addressed some of these end-points (risk of death, major adverse cardiovascular events, and infection) in patients undergoing hemodialysis and has just been published [149,150]. A high-dose regimen of i.v.…”
Section: Treatment Strategiesmentioning
confidence: 99%
“…Furthermore, 43% of patients with identified anaemia and 15% of those without anaemia from the total cohort had iron and/or folate deficiency and survival was worse in deficient patients [3]. Hence, iron may be an important substrate for optimal cardiac function and reduction in cardiac risk as noted in the recent PIVOTAL study [4].…”
mentioning
confidence: 90%
“…The PIVOTAL trial [16], the largest prospective randomized study, recruiting 2171 HD patients, has recently provided important safety results. This study has demonstrated, for the first time, that the use of a liberal, proactive higher dose IS regimen [aimed at targeting higher ferritin and transferrin saturation (TSAT) values] was superior to the use of a low-dose, reactive IS regimen and was associated with a lower risk of major cardiovascular events (acute myocardial infarction, stroke, hospitalization for heart failure or mortality) and did not increase the risk of all-cause mortality.…”
Section: Introductionmentioning
confidence: 99%